2021
DOI: 10.3389/fnmol.2021.759729
|View full text |Cite
|
Sign up to set email alerts
|

Arginine and Arginine-Rich Peptides as Modulators of Protein Aggregation and Cytotoxicity Associated With Alzheimer’s Disease

Abstract: A substantial body of evidence indicates cationic, arginine-rich peptides (CARPs) are effective therapeutic compounds for a range of neurodegenerative pathologies, with beneficial effects including the reduction of excitotoxic cell death and mitochondrial dysfunction. CARPs, therefore, represent an emergent class of promising neurotherapeutics with multimodal mechanisms of action. Arginine itself is a known chaotrope, able to prevent misfolding and aggregation of proteins. The putative role of proteopathies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 194 publications
3
19
1
Order By: Relevance
“…Moreover, the SARS-CoV-2 arginine motif activates TMEM16F, a physiological placental fusogen that was implicated in the aberrant glial phagocytosis of neurons and synapses, emphasizing a novel arginine-linked neurodegeneration mechanism ( Lin et al., 2021 ). Furthermore, as arginine-rich peptides were reported to induce cytotoxicity in AD, viral arginine may be the missing link between cell-cell fusion and neurodegenerative disorders ( Mamsa and Meloni, 2021 ).…”
Section: Cell-cell Fusion the Molecular Actorsmentioning
confidence: 99%
“…Moreover, the SARS-CoV-2 arginine motif activates TMEM16F, a physiological placental fusogen that was implicated in the aberrant glial phagocytosis of neurons and synapses, emphasizing a novel arginine-linked neurodegeneration mechanism ( Lin et al., 2021 ). Furthermore, as arginine-rich peptides were reported to induce cytotoxicity in AD, viral arginine may be the missing link between cell-cell fusion and neurodegenerative disorders ( Mamsa and Meloni, 2021 ).…”
Section: Cell-cell Fusion the Molecular Actorsmentioning
confidence: 99%
“…One of the most commonly used excipients to suppress protein aggregation is L-arginine [ 7 , 8 , 9 , 10 , 11 , 12 ]. Even though the mechanism of the beneficial effect of arginine is still not completely understood, several experimental and theoretical studies have been conducted to elucidate its role.…”
Section: Introductionmentioning
confidence: 99%
“…Already in 2017, Nadimidla and colleagues found that poly-L arginine hydrochloride inhibited aggregation of PHF6 and a PHF6* containing fragment as well as of Tau mutant protein P301L (Nadimidla et al 2017). The impact of arginines and arginine-rich peptides is very interesting and was reviewed by Mamsa and Meloni in 2021 in detail (Mamsa and Meloni 2021).…”
Section: Discussionmentioning
confidence: 99%